THE EFFECT OF MUSIC ON THE EMOTIONS OF ISLAMIC STUDENTS - Wawan Nopriansa; Hanna Azzahra Nabella; Ardiansyah; Yustika Pratiwi; Dicky Wandira Aditya Putra; Shintya Nabilla; Indani Woronia Nure; Laili Fatimatuzzahro (CV. Doki Course and Training, 2023)
Music is the art of sound arranged in patterns that are pleasing to our ears and convey emotions and moods. The purpose of this study was to determine the effect of music on students' emotions. This experimental research design used the One Group Pretest Posttest Design. This research was conducted on students of the Raden Fatah State Islamic University Palembang semester 5, Faculty of Psychology class of 2020. Data analysis used the Paired Sample Test technique with assistance using SPSS. The results of this study indicate that the value is Sig. (2-tailed) = 0,015 (p <0,05). So it can be concluded that there is a significant difference in the effect of music on students' emotions before and after being given treatment, that when given treatment in the form of listening to and watching the MV